Golovanenko E. A., Skvarcha O. N. Expansion of semantic volume of the word "nostalgia" in Russian and its inclusion in the new circle of semantic association - Golovanenko E. A.; Skvarcha O. N. (Philological Treatises, 2020)
The article considers one of the basic semantic processes occurring in the modern Russian lexicon - generalization of a word meaning. It contains the analysis of a lexeme which as a result of this process starts to be used in various areas and contexts.